Relações entre currículo, identidade e prática profissional em início de carreira de egressos do curso de Letras da UFSCar - Tomazella, Carla Maluf (Universidade Federal de São Carlos, 2017)
Many recently graduated language teachers complain about the lack of proficiency in the foreign language and the sense of pedagogical unpreparedness for the teaching practice, which produces a kind of "teacher malaise" (ESTEVE, 1999). Thus, the present research discusses the concept of professional identity of Spanish teachers, seeking to understand some aspects of its constitution in a specific context of initial university education. Based on the assumption that the constitution of professional identities is developed in a social and historical process, we sought to understand, along with a group of undergraduates of the Spanish-language teacher training course of the Federal University of São Carlos (UFSCar), which aspects of their initial academic education contributed to the configuration of their identities. From the perceptions of the undergraduates expressed in a semistructured questionnaire, our analyzes point out some of the aspects related to the constitution of their professional identities and contrast these aspects with the curricular proposal of the Pedagogical Project of the course - in order to reflect on the implications that such structuring can have on the constitution of the identities of the Spanish teachers who graduated in UFSCar - and with results of other researches developed in Brazil that study the same theme. The research is characterized as a case study, of exploratory and qualitative nature, whose analyzes are based on the Content Analysis methodology (BARDIN, 1977). The research is based theoretically in the field of Applied Linguistics, more specifically in authors that study the training of teachers as critical professionals (ALMEIDA FILHO, 1999; CASTRO, 1999) and who deal with the theory-practice relationship in language teacher training (VIEIRA-ABRAHÃO, 2001, 2004; ALMEIDA FILHO, 1999; GIMENEZ, 2004, EL-KADRI, 2010). As results, our analysis points to a change in El Kadri's (2010) perspective that the professional identity of Brazilian Spanish teachers is strongly marked by a sense of "lack of linguistic proficiency", since the aspects perceived by the undergraduates of the course researched relates mainly to the "feeling of pedagogical unpreparedness" and, therefore, to aspects related to pedagogical knowledge. Thus, PIBID's proposal as an institutionalized teacher-initiation program that may make it possible for future teachers to build their knowledge about being a teacher in practice and from their own experiences (GIMENEZ, 2004) is relevant, as it may lead to a possible overcoming of the severance that has long been established between theory and practice in teacher-training courses.
Keywords: Formação de professores; Identidade profissional docente; Língua espanhola; Projeto pedagógico; Teacher training; Professional teacher identity; Spanish language; Pedagogical project; LINGUISTICA, LETRAS E ARTES::LINGUISTICA